The Effect of Company Behavior on Financial Success in Manufacturing in Banten Province - Safii, Mohamad; Aspiranti, Tasya; Nurhayati, Nunung; Amaliah, Ima (Publisher Cv. Inara, 2026)
This study explores the influence of firm behavior regarding financial performance in manufacturing companies located in Banten Province during the period 2021–2024. Employing a numerical approach and Structural Equation Modeling (SEM) with a covariance-based method, the research examines the influence of three behavioral dimensions—transformational leadership, organizational culture, and managerial strategy—regarding essential financial metrics such as ROA, ROE, and NPM. The findings reveal that overall firm behavior exerts a substantial beneficial impact on financial performance, confirmed by strong goodness-of-fit indicators. Further analysis indicates that transformational leadership, organizational culture, and managerial strategy each contribute meaningfully to financial outcomes. These findings highlight the critical role of behavioral factors in enhancing profitability and competitiveness. The study offers theoretical contributions to behavioral governance literature and practical implications for leadership development, cultural alignment, and adaptive strategic management in dynamic market environments. Limitations include regional scope and reliance on secondary data future research should employ longitudinal and cross-industry designs for broader generalizability.